Pengaruh Pemahaman Peraturan Perpajakan Dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak: Studi Kasus pada Kantor Pelayanan Pajak Pratama Bogor - Desi Rachmawati Kencana Sari; Eha Hasni Wahidhani; Wartoyo Hadi (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This research aims to test and analyze the influence of understanding tax regulations and tax rates on taxpayer compliance (case study at the Bogor Pratama Tax Service Office). This research is quantitative. Data was collected using a questionnaire technique with a sampling technique using convenience sampling. The data analysis techniques used are descriptive, classical assumption analysis tests, multiple linear regression tests, hypothesis tests, and coefficient of determination tests. The results of this research show that understanding tax regulations and tax rates has a significant and simultaneous effect on taxpayer compliance at KPP Pratama Bogor.